Assessing tropical cyclone risks using geospatial techniques. (September 2018) - Hoque, Muhammad Al-Amin; Phinn, Stuart; Roelfsema, Chris; Childs, Iraphne
Abstract: Tropical cyclones are one of the most catastrophic natural disasters, regularly affecting coastal areas across the world. The intensity and extent of impacts by these disasters have remained very high throughout history. An appropriate mapping approach is essential for producing detailed risk assessments to plan for, and reduce the future impacts of cyclones on people, property and the environment. This study developed and evaluated a spatial multi-criteria approach for mapping the risk levels of areas to tropical cyclone impacts using remote sensing, field data and spatial analysis at a local scale covering <1000 km 2 . We used the Sarankhola Upazila (151 km 2 ), a local government area, from coastal Bangladesh to test the applicability of this approach. Three risk components: vulnerability and exposure; hazard; and mitigation capacity, and their 14 relevant criteria were considered. Thematic raster map layers were prepared for every criterion and weighted using an Analytical Hierarchy Process (AHP). A weighted overlay technique was used for generating individual maps for every risk component and then risk map was produced from them. The resulting maps successfully identified the spatial extents and levels (very high, high, medium, low, and very low) of risk. Our results indicate that eastern, south and south-western parts of the study area are likely to be subject to higher risk from tropical cyclone's surge height, strong wind and intensive rainfall than other parts. The approach provided was validated by confidence level assessment and a map of past cyclone impacts. Our preliminary findings indicate this approach has the potential to assess risks from tropical cyclone impacts in the affected countries by producing risk maps able to be used by policymakers and administrators. Highlights: The study provided a spatial multi-criteria cyclone risk mapping approach. AHP was found more effective to support the multi-criteria decision making process. The incorporation of mitigation capacity significantly influenced the risk results. Mapping approach successfully identified the spatial extents and levels of cyclone risk.